Co-design and content validation of psychosis care assessment material for medical, pharmacy, nursing, and occupational therapy curricula - Jenny Chen; Jack Charles Collins; Justin Newton Scanlan; Andrea McCloughen; Rosa Howard; Claire Ashton-James; Claire L. O’Reilly; Rebekah J. Moles; Tina X. Ung; Carl R. Schneider; Bandana Saini; Jennifer Ong; et al. (BMC Medical Education)
Abstract Background Despite high disease burden and heightened suicide risk associated with psychosis, psychosis education is lacking in healthcare curricula, potentially hindering students’ willingness, and confidence to provide psychosis care as future healthcare professionals. This study aimed to co-design and content validate psychosis care assessment material for medical, pharmacy, nursing, and occupational therapy curricula. Methods A nominal group technique (NGT) meeting was conducted to generate and rank ideas among people with lived/living experience of mental illness. Prioritised ideas were used to create simulated role-play scenarios for each discipline, by discipline experts. The developed scenarios underwent content validation by content experts, whereby the content validity index was computed for relevance and clarity. Results The four highest ranked ideas based on rank scores and accumulated rank score sums were selected during the NGT meeting and used to guide the development of four role-play scenarios focusing on antipsychotic medication side effects, suicide risk, paranoia and delusions, and visual hallucinations. Discipline experts created scenario outlines and rubrics for each selected idea. Content validity indices of all items were deemed satisfactory, ranging from 0.8 to 1. Written feedback for each role-play scenario was considered and scenarios/rubrics were modified accordingly. Conclusion Overall, this study provides a framework for partnering with mental health stakeholders to co-design and validate psychosis care assessment material for healthcare curricula. Through the integral contribution of people with lived/living experience and clinicians, authentic scenarios which reflect real-life practice have been developed. Future research is required to evaluate the newly developed materials in educational setting.